Factors associated with the coexistence of anemia and undernutrition among children aged 6–59 months in Mali, 2023/24: A multilevel mixed-effects analysis - Halid Worku Jemil; Sonia Worku Semayneh; Eyob Tilahun Abeje; Altaseb Beyene Kassaw; Gosa Mankelkl; Anmut Endalkachew Bezie; Adisu Meles Kabtyimer (PLoS ONE, 2026)
Introduction coexistence of anemia and undernutrition is a major public health concern among children in Mali. However, there is a lack of study looking into the relationship between undernutrition and anemia among children in Mali. Therefore, this study was conducted by using multilevel analysis to identify significant factors associated with the coexistence of anemia and undernutrition among children. Methods A cross-sectional design was conducted from Mali Demographic and Health Survey data from 2023/24. STATA 17 was used for data summarization and analysis. The model was evaluated using the intra-class correlation coefficient (ICC), median odds ratio (MOR), likelihood ratio (LR), and deviance. Variables with a p-value less than 0.2 in the bi-variable logistic regression analysis were taken into account for the next multilevel analysis. In the multilevel analysis, significant factors were presented using the Adjusted Odds Ratio (AOR) along with the 95% Confidence Interval (CI). Results The prevalence of the coexistence of anemia and undernutrition among children was 26.3% (CI: 25.2%, 27.4%). According to the multilevel logistic regression result, mothers aged 25–34 years (AOR = 1.41; 95% CI: 1.01, 1.96), no education (AOR = 1.51; 95% CI: 1.19, 1.91), primary education (AOR = 1.39; CI: 1.05, 1.84), not covered by health insurance (AOR = 2.18; 95% CI: 1.05, 2.47), rural residents (AOR = 1.46; 95% CI: 1.16, 1.84), and short maternal stature (AOR = 1.83; 95% CI: 1.49, 2.27) were associated with an increased odds of the coexistence of anemia and undernutrition among children. In contrast, tall maternal stature (AOR = 0.29; 95% CI: 0.22, 0.36) and children aged 37–47 months (AOR = 0.70; 95% CI: 0.50, 0.96) were associated with decreasing the odds of the coexistence of anemia and undernutrition among children. Conclusion In Mali, the coexistence of anemia and undernutrition contributes to mortality and related complications among children. The finding from this study revealed that children whose mothers were aged 25–34, mothers without formal education, mothers without primary education, mothers whose health was not covered by health insurance, children who lived in rural areas, and maternal short stature were associated with increased odds of the coexistence of anemia and undernutrition among children. In contrast, tall maternal stature and children aged 37–47 were associated with decreasing the odds of the coexistence of anemia and undernutrition among children.